115 DIURETIC DOSE TRAJECTORIES IN DILATED CARDIOMYOPATHY: PROGNOSTIC IMPLICATIONS. (15th December 2022) - Nuzzi, Vincenzo; Cannatà, Antonio; Pellicori, Pierpaolo; Manca, Paolo; Stolfo, Davide; Gregorio, Caterina; Barbati, Giulia; Bromage, Daniel I; Mcdonagh, Theresa; Cleland, John Gf; Merlo, Marco; Sinagra, Gianfranco
Abstract: Background: For patients with heart failure, prescription of loop diuretics (LD) and higher doses are associated with adverse prognosis. We investigated LD dose trajectories and their associations with outcomes in patients with dilated cardiomyopathy (DCM). Methods: Associations between outcomes and both furosemide equivalent dose (FED) at enrolment and change in FED in the subsequent 24 months were evaluated. According to FED trajectory, patients were divided in i) dose↑ (FED increase by ≥50% or newly initiated); ii) dose↓ (FED decrease by ≥50%); iii) stable dose (change in FED by <50%); iv) never-users. Primary outcome was all-cause-death/heart transplantation/ventricular-assist-device/heart failure hospitalization. Secondary outcome was all-cause-death/heart transplantation/ventricular-assist-device. Results: Of 1, 131 patients enrolled, 738 (65%) were prescribed LD at baseline. Baseline FED was independently associated with outcome (HR per 20mg increase: 1.12 [95% CI 1.04-1.22, p=0.003]. Of the 908 with information on FED within 24 months from enrolment, 31% were never-users; 29% dose↓; 26% stable dose and 14% dose↑. In adjusted models, compared to never-users, stable dose had a higher risk of primary outcome (HR 2.42 [95% CI: 1.19-4.93], p=0.015), while dose↑ had the worst prognosis (HR 2.76 [95% C.I. 1.27-6.03], p=0.011). The results were consistent for the secondary outcome. Compared to patients who remained on LD, discontinuation of LD (143, 24%) was associated with improved outcome (HR 0.43 [95% C.I. 0.28-0.65], p<0.001). Conclusions: In a large cohort of patients with DCM, LD use and increasing FED are powerful markers of adverse outcomes. Patients who never require LD have an excellent prognosis.